Kingdom Fungi approaches in Teacher Portal Lesson Plans and Science Textbooks (Research, Society and Development, 2021)
Objective: To analyze three approaches on the Fungi kingdom in the classroom plans of the Teacher Portal and in Science Textbooks for the seventh year of elementary school, in addition to the work guidelines on this subject according to the Common National Curriculum Base (BNCC). Methodology: This is a documentary research, qualitative in nature through content analysis, carried out by selecting Textbooks (LD) on Elementary Education Sciences published in 2014 and 2015. With the terms, “Fungi kingdom”; “Fungi” and “Fungi and elementary school” searched for lesson plans on the Teacher Portal (PP) of the Ministry of Education. Results and discussion: Eight textbooks and 32 of the lesson plans were analyzed in three approaches: health, visual and pedagogical. In health, pathogenic fungi are little explored in class plans. They receive greater prominence in LD. In the visual approach, we analyzed the number of images, caption (presence or absence), scale (absence, macroscopic or microscopic), images inserted in the text or displaced, presence of real images (photo) and diagrams. 112 images were counted in the 8 analyzed LDs. In the pedagogical approach, we chose to verify the presence of practical classes. We classify activities into 4 categories: Culture, Observation, Fermentation and Absence. Final considerations: The comparative analysis of what is available in the textbooks and in the lesson plans with what is presented in the BNCC shows a decrease in the Kingdom Fungi approaches, limiting them only to the food chains studied in the fourth year of elementary school.